If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -4a = 2a + 1 + -5a Reorder the terms: 4 + -4a = 1 + 2a + -5a Combine like terms: 2a + -5a = -3a 4 + -4a = 1 + -3a Solving 4 + -4a = 1 + -3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3a' to each side of the equation. 4 + -4a + 3a = 1 + -3a + 3a Combine like terms: -4a + 3a = -1a 4 + -1a = 1 + -3a + 3a Combine like terms: -3a + 3a = 0 4 + -1a = 1 + 0 4 + -1a = 1 Add '-4' to each side of the equation. 4 + -4 + -1a = 1 + -4 Combine like terms: 4 + -4 = 0 0 + -1a = 1 + -4 -1a = 1 + -4 Combine like terms: 1 + -4 = -3 -1a = -3 Divide each side by '-1'. a = 3 Simplifying a = 3
| -24+2=m-6 | | 6h-10=15h-80 | | 14=2+2s | | 3x-11=x+21 | | 4+4b=34.4 | | 24=6+7x-5x | | 14x(5-6)= | | 2(y+1)=y-4 | | 2+6s=26 | | 9y-13y=-10-14 | | 19-12a=79 | | x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 | | 3a-19=-49 | | 2(x-3)=34 | | 4x-23=3x-5 | | 6x+9-5x=12 | | 42a^4+60a^3=0 | | 5z+7=6(z-2)-4(2z-3) | | -39=6+5t | | 25x+5(x+5)+10(x-9)=3,115 | | 3(x)=18 | | (5x^4)(25x^2)= |